The Application of Contribution Margin in Determining Products and Product Combinations That Produce Most Maximum Profit by Linear Programming Method - Syafril Djaelani (Perkumpulan Dosen Manajemen Indonesia, 2020)
Abstract, This study aims to determine the products and product combinations that produce the maximum profit produced by PT.X. Production planning undertaken by managers to achieve the desired level of profit with limited resources using linear programming methods is appropriate. The type of research used in this study is descriptive with a quantitative approach. This research was compiled using library research methods (library research) by conducting data simulations so that a conclusion was obtained. The results show that the contribution margin is very useful in making product decisions and product combinations that produce the maximum profit.